Exploring the Formation of Relational Collaboration among Competitors - Nur Alamzah; Badri Munir Sukoco; Indrianawati Usman (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This paper aims to explore how a relational collaboration process is formed among bag and suitcase craftsmen in an Industrial Village in Indonesia. Design/Methods/Approach: The study is a qualitative case study formulated from nine informants interviewed with different roles, from the initiators, actors, and community leaders to local government agencies. Information collected is analyzed using the Gioia method with the three stages of analysis: concepts, themes, and dimensions. Findings: Different from previous research, which stated that three perspectives of the interaction form of the dynamics of business competition, namely rivalry, competitive-cooperation, and relational, can only be manifested mutual-exclusively according to a certain cultural context, this study finds that those perspectives can be manifested as an evolutionary stage. which we label as "relational-collaboration. "Collaboration is an inseparable process following dynamic changes and adjusting the challenges and opportunities in each competitive interaction change. The changing evolution processes begin from rivalry competition to competitive cooperation and turn again into relational collaboration. Rivalry interaction through price wars has had a negative impact on all craftsmen and even on their social environment. The emergence of an awareness of the price-war impact made a small number of craftsmen initiate to work together through the formation of a cooperative to support their capital business. Although initially, only a few craftsmen became members, the commitment of the initiator members led other craftsmen to join in. This process continues to grow until the formation of relational collaboration among craftsmen in response to orders in large quantities within and outside the country. Originality: Limited study found to discuss how relational collaboration is formed, especially those focusing on the business cluster. This study expects to fill the gap by exploring the empirical aspect of forming relational collaboration among competitors.